Collectivization of Agriculture in 1928s-1930s: Role of “Light Cavalry” - A. A. Slezin (Научный диалог, 2019)
The contradictory role of the Komsomol “light cavalry” at the initial stage of the continuous collectivization of agriculture in the USSR is analyzed. The main sources were the materials of the Russian state archive of social and political history and propaganda brochures of the 1920s-1930s. The methodological basis of the study is the classical principles: historicism, objectivity, social approach, alternative. The theory of modernization is used, which is understood as the transition from agrarian to industrial society. As a theoretical platform, the author appeals to the theory of nationalization of the Komsomol: the Komsomol is considered as a kind of Soviet “Ministry of youth”, a link between the state and youth. It is shown that in the conditions of shortage of highly qualified personnel and mismanagement in hastily created collective farms, the authorities had to involve inexperienced boys and girls in the implementation of the function of social control. It is noted that “cavalrymen” watched the condition of working cattle, forges, warehouses, bulk items, even the preparation of production plans. However, as shows the author, useful activities for the elimination of economic disadvantages were accompanied by obvious excesses, search not only for obvious, but for imaginary enemies. Particular attention is paid to the identification of the specifics of the “light cavalry” after the publication of Stalin’s article “Dizziness from success.”